Targeting Glutaminolysis: New Perspectives to Understand Cancer Development and Novel Strategies for Potential Target Therapies - Wang, Zhefang; Liu, Fanyu; Fan, Ningbo; Zhou, Chenghui; Li, Dai; Macvicar, Thomas; Dong, Qiongzhu; Bruns, Christiane J.; Zhao, Yue (Frontiers in Oncology, 2020)
Metabolism Rewiring is a hallmark of cancer. As one of the most abundant free amino acids in human blood, glutamine supports bioenergetics and biosynthesis, tumor growth, and production of antioxidants through glutaminolysis in cancer. In glutamine dependent cancer cells, more than half of the TCA metabolites are derived from glutamine. Glutaminolysis controls the process of converting glutamine into TCA cycle metabolites through the regulation of multiple enzymes, while glutaminase shows the importance as the very first step in this process. Targeting glutaminolysis through glutaminase inhibition emerges as a promising strategy to disrupt cancer metabolism and tumor progression. Here, we review the regulation of glutaminase and the role of glutaminase in cancer metabolism and metastasis. Furthermore, we highlight the glutaminase inhibitor based metabolic therapy strategy and their applications in clinical set up.